Supply the demand: Assessment of the feasibility of local nonurologists in relieving the burden of chronic indwelling catheters in a low-income country - Bobrowski, Adam; Nayan, Madhur; Heimrath, Olivier; Goche, Duncan; Ludzu, Enok; Singal, Rajiv K. (Canadian Urological Association Journal, 2020)
Introduction: Despite the high prevalence rates of urinary retention in sub-Saharan Africa, regional deficiencies in urological care have culminated in inadequate medical management and a backlog of urology cases. Our study examined the efficacy and safety of a surgical camp enlisting local non-urologists performing simple open prostatectomy on the rate of chronic catheter usage secondary to urinary retention. Methods: We reported on a prospective case series of patients with chronic indwelling catheters who underwent open simple prostatectomy during a one-week urology camp in the Machinga District of Malawi. All operations were performed by a locally trained general surgeon and a clinical officer. Results: Twenty-three (47.9%) of 48 male patients with urinary retention assessed for eligibility for open simple prostatectomy were deemed eligible and underwent the procedure. Of the patients who underwent an open simple prostatectomy, histopathological findings demonstrated benign prostatic hyperplasia in 19 patients (82.6%), while six patients (26.1%) had coincidental malignancy. At postoperative followup, the entire cohort was catheter-free and reported regular sexual activity and the ability to return to work, while 87.0% noted improvements in social integration and 34.8% cited higher self-esteem. Two patients required treatment for infection and one patient experienced fascial dehiscence. Two months following prostatectomy, all patients were catheter-free and able to void independently. Conclusions: Local surgical practitioners without formal urology training can successfully perform open simple prostatectomy to relieve patients of chronic indwelling catheters and assist in addressing the disease burden in a low-resource setting.